2007
DOI: 10.1243/0954406jmes519
|View full text |Cite
|
Sign up to set email alerts
|

Rapid calculation of the pressures and clearances in rough, rolling-sliding elastohydrodynamically lubricated contacts. Part 1: Low-amplitude, sinusoidal roughness

Abstract: Surface roughness in elastohydrodynamically lubricated (EHL) contacts may have a significant effect on component life and there is a need to be able to assess its effects quickly. This article describes a rapid calculation method, which provides accurate results where the amplitude of the roughness is relatively low and which gives good indications of the likely behaviour for higher amplitudes. In the first part, the effect of low-amplitude, sinusoidal roughness is examined, and it is shown that the behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 17 publications
2
59
0
Order By: Relevance
“…In order to properly consider sliding, a non-Newtonian scheme is required; therefore, in the present article the scheme developed by Hooke (27) and Hooke, et al (28) and described in detail in Morales-Espejel, et al (21) is followed. As described in these references, in the center of an EHL contact, variations of the microgeometry with small amplitude will produce products of fluctuations (pressures and clearances) and products of derivatives in the Reynolds equation that can be neglected; thus, the Reynolds equation can be written as,…”
Section: Lubrication Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to properly consider sliding, a non-Newtonian scheme is required; therefore, in the present article the scheme developed by Hooke (27) and Hooke, et al (28) and described in detail in Morales-Espejel, et al (21) is followed. As described in these references, in the center of an EHL contact, variations of the microgeometry with small amplitude will produce products of fluctuations (pressures and clearances) and products of derivatives in the Reynolds equation that can be neglected; thus, the Reynolds equation can be written as,…”
Section: Lubrication Modelmentioning
confidence: 99%
“…Hooke, et al (28) suggested an exponential decay with respect to the inlet (x = x + a) location. Because the waves propagate with the average speed of the lubricant, effectively they will have a wavenumber in x such that ω x ≈ ω x (u 2 /ū).…”
Section: Lubrication Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The part of the model used in this study was published by Hooke [35][36][37] and other part by Lubrecht and Venner [29]. Inside an EHL contact a harmonic wave of amplitude and phase expressed by complex number A i is change to A d .…”
Section: Prediction Schemementioning
confidence: 99%